(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The chloroform extract of L. speciosa andhydro alcoholic extract of coccinia grandis these two extracts major ingredients composed tablet formulation was evaluated for antioxidant and antimicrobial activity. Aim is that this tablet formulation may be useful for commercial purpose for treatment of mouth ulcer, antimicrobial, antioxidant, anticancer, antidiabetic, wound healing & anti-inflammatory activity. So we are evaluated this tablet formulation antioxidant and antimicrobial activity successfully. Materials and Methods: The antioxidant activity of combined tablet formulation of chloroform extract of L. Speciosa and Hydro-alcoholic extract of Coccinia grandis was investigated by DPPH and H2O2 assay. Result: The study showing that tablet formulation of chloroform extract of L. Speciosa and Hydro-alcoholic extract of Coccinia grandis has better antioxidant activity. Flavonoid as well as phenolic contents were found most in above formulation. It confirmed high radical scavenging activity. Conclusion: The study discovered the expected of the tablet formulation of chloroform extract of L. Speciosa and Hydro-alcoholic extract of Coccinia grandis as natural sources of significant antioxidants so it can be use commercial purpose.